Leadership and administrative concepts and their relationship to role behavior of public elementary school principals in the City of Manila - Ebreo, Maxima D. (Cruz) 1927- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1966)
This study determines the leadership and administrative concepts of public elementary school principals and how they relate to the principal's role behavior. The researcher found that the leadership and administrative concepts of the public elementary school principals are significantly higher than all their rater respondents. It is highly probable that they treat the two terms synonymously.
Thesis (M.Ed.)--University of the Philippines
Keywords: School superintendents and principals